Testing a pain self-management intervention by exploring reduction of analgesics' side effects in cancer outpatients and the involvement of family caregivers: a study protocol (PEINCA-FAM) - Sabine Valenta; Rebecca Spirig; Christine Miaskowski; Kathrin Zaugg; Elisabeth Spichiger (BMC, 2018)
Abstract Background Pain is one of cancer patients' most frequent and distressing symptoms; however, analgesics' side effects often increase symptom burden. Further, with the home rapidly becoming the primary cancer care setting, family caregivers (FCs) commonly play central roles in patients' pain self-management, but with little or no preparation. One US-tested intervention, the PRO-SELF© Plus Pain Control Program (PCP), designed to support cancer outpatients and their FCs in pain self-management, is currently being tested in the Swiss multi-centre PEINCA study. The current PEINCA-FAM study is a sub-study of PEINCA. The aims of PEINCA-FAM are: a) to test the efficacy of the adapted German PRO-SELF © Plus PCP to reduce side effects of analgesics; b) to enhance patients'/FCs' knowledge regarding cancer pain; and c) to explore FCs' involvement in patients' pain self-management. Methods This mixed methods project combines a multi-centre randomized controlled clinical trial with qualitative data collection techniques and includes 210 patients recruited from three oncology outpatient clinics. FCs involved in patients' pain self-management are also invited to participate. After baseline evaluation, eligible participants are randomized to a 6-week intervention group and a control group. Both groups complete a daily pain and symptom diary. Intervention group patients/FCs receive the weekly psychoeducational PRO-SELF© Plus PCP interventions; control group patients receive usual care. After completing the six-week study procedures, a subsample of 7-10 patients/FCs per group and hospital (N = 42-60) will be interviewed regarding their pain management experiences. Data collection will take place from April 2016 until December 2018. An intent-to-treat analysis and generalized linear mixed models will be applied. Qualitative data will be analysed by using interpretive description. Quantitative and qualitative results will be combined within a mixed method matrix. Discussion In clinical practice, specially trained oncology nurses in outpatient clinics could apply the intervention to reduce side effects and to enhance patients'/FCs' self-efficacy and pain management knowledge. Trial registration The PEINCA study is registered in the Clinical Trials.gov site (code: NCT02713919, 08 March 2016).